International relations teaching game and development of students’ professional competences: The Simulation «State Foreign Policy». - T. N. Litvinova (Vestnik MGIMO-Universiteta)
The training game “Foreign policy of a state”, developed by the author in 2002, is presented in the article. Teaching techniques and ways of practical use of the game in special courses for international relations students of Far East State Technical University (Vladivostok, Russia) and Institute of Business and Law (Moscow, Russia) are examined. The author analyzes the results of his educational experiment from the perspective of competency building approach and proposes ways of wider use of the game “Foreign policy of a state” in order to develop professional competencies of graduate international relations students.